Some obstacles of biletaral business relations between Kazakhstan and China (Халықаралық қатынастар және халықаралық құқық сериясы, 2020)
The main goal of the article is to reassess and analyze difficulties and obstacles in the way of businessrelations between the Republic of Kazakhstan and the People's Republic of China in the context ofthe international economic crisis. Kazakhstan and China are historically and geographically neighbors,and it is clear that we will enter into political, cultural, economic and military relations with a neighboringcountry, whether we want it or not. At present, Kazakhstan has such views as anti-Chinese sentiment,the “Chinese threat”, and there are reasons for that. If we take into account our eternal neighborhood andclose trade and economic relations, we should consider China, a country with huge economic potential,not only in terms of threats and fears, but also as a new opportunity for Kazakhstan, while maintainingthe integrity and sovereignty of the country. Since gaining independence, Kazakhstan has establishedfriendly and partnership relations with the People's Republic of China, having completely resolved theissue of the border between the two countries, and today has established relations as a new strategicpartner. However, there are key problems between the two countries. We see that there are many political,legal, regulatory, cultural and ideological barriers to the development of business relations. Thisarticle can help us to understand some of them.Key words: Republic of Kazakhstan, People's Republic of China, business relations, foreign policy.